Penerapan Portfolio Assessment untuk Kepentingan Guru Mensinyalir Bakat Siswa Ditinjau dari Sekolah Negeri dan Swasta - Hariyanti Djafar; Fahyudin Jumat (Peneliti.net, 2021)
This study aims to determine the extent of the implementation of portfolio assessment in public and private schools, the difficulty of implementing portfolio assessment based on the teacher's perspective. This research was conducted using a qualitative descriptive approach. The data collection process was carried out in three stages, namely observation, interviews, and documentation. Meanwhile, at the data analysis stage, the researcher utilized data from the results of observation, interviews, and documentation, and then followed up with 3 stages, namely; data reduction, data presentation, and drawing conclusions. The informants of this study were 3 teachers at each SMA N 5 City of Tidore Islands, YASMU High School, and SMA 8 City Tidore Islands. The results showed that there were differences in the implementation of portfolio assessment between schools with state status and schools with private status. In public schools, the implementation of portfolio assessment is more effective and programmed so that the learning outcomes and talents of students are more easily recognized and guided on an ongoing basis, while in private schools it is not. Difficulties in implementation are more likely in private schools caused by external and internal factors.